Thoracic Society of Australia and New Zealand oxygen guidelines for acute oxygen use in adults: 'Swimming between the flags'1. Issue 8 (November 2015) - Beasley, Richard; Chien, Jimmy; Douglas, James; Eastlake, Leonie; Farah, Claude; King, Gregory; Moore, Rosemary; Pilcher, Janine; Richards, Michael; Smith, Sheree; Walters, Haydn
Abstract The purpose of the Thoracic Society of Australia and New Zealand guidelines is to provide simple, practical evidence‐based recommendations for the acute use of oxygen in adults in clinical practice. The intended users are all health professionals responsible for the administration and/or monitoring of oxygen therapy in the management of acute medical patients in the community and hospital settings (excluding perioperative and intensive care patients), those responsible for the training of such health professionals, and both public and private health care organizations that deliver oxygen therapy.